2017
DOI: 10.21911/aai.16
|View full text |Cite
|
Sign up to set email alerts
|

Food Hypersensitivity in Atopic Dermatitis During Infancy: Skin Prick Testing for Whom?

Abstract: ÖZGiriş: Atopik dermatit (AD) bebeklik döneminde sık görülen bir hastalıktır. Yaşamın ilk 6 ayında, özellikle ilk 3 ayında başvuran AD'li hastalarda besin duyarlılığı konusunda veri kısıtlıdır. Çalışmada AD tanısı almış bebeklerde başvuru zamanına göre besin duyarlılığı(BD) sıklığının ve ilişkili faktörlerin ortaya konulması amaçlanmıştır.Gereç ve Yöntem: Çalışmamıza S.B. Ankara Eğitim Araştırma Hastanesi Çocuk Allerji ve İmmünoloji Kliniği'ne başvuran AD'li bir yaşından küçük hastalar dahil edildi. Hastaların… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
0
1
Order By: Relevance
“…In a study examining 110 AD patients younger than 1 year old, serum total IgE and serum eosinophil levels were found to be higher in the food sensitive group, and it was reported that the serum total IgE and serum eosinophil level elevations provided a prediction for food sensitivity in patients with severe AD. [ 40 ] In our study, on the contrary, no statistically significant correlation was found between the severity of AD, serum total IgE level, percentage of eosinophils, and food sensitivity. Ciğerci Günaydın et al [ 22 ] reported in their study that there was no difference between food sensitivity and total serum IgE and serum eosinophil levels, similar to our results.…”
Section: Discussioncontrasting
confidence: 86%
“…In a study examining 110 AD patients younger than 1 year old, serum total IgE and serum eosinophil levels were found to be higher in the food sensitive group, and it was reported that the serum total IgE and serum eosinophil level elevations provided a prediction for food sensitivity in patients with severe AD. [ 40 ] In our study, on the contrary, no statistically significant correlation was found between the severity of AD, serum total IgE level, percentage of eosinophils, and food sensitivity. Ciğerci Günaydın et al [ 22 ] reported in their study that there was no difference between food sensitivity and total serum IgE and serum eosinophil levels, similar to our results.…”
Section: Discussioncontrasting
confidence: 86%
“…In a study involving 110 infants with AD, it was found that 70% were male. 12 In our study, food allergy was found in 60.60% of patients with AD. In a study conducted in Korea, food allergy was found in 37.1% of infants with AD aged 0-5 months and in 38.5% of infants aged 6-11 months.…”
Section: Discussionsupporting
confidence: 47%